Profile Anti-Inflammatory Mechanisms of Moringa Leaves: A Review of Preclinical and Clinical Studies - Pauzan, Pauzan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Moringa oleifera leaves have long been recognized in traditional medicine for their anti-inflammatory properties. This review aims to comprehensively evaluate current scientific evidence from both preclinical and clinical studies regarding the anti-inflammatory mechanisms of moringa leaves. A systematic search of the literature was conducted using databases such as PubMed, Scopus, and Google Scholar, covering studies published up to 2025. Preclinical findings indicate that moringa leaf extracts exhibit significant anti-inflammatory activity through various mechanisms, including inhibition of prostaglandin synthesis, suppression of pro-inflammatory cytokines such as TNF-α and IL-6, and modulation of the NF-κB signaling pathway. In vivo animal models further demonstrate reductions in edema and inflammatory cell infiltration. Early-phase clinical trials suggest potential therapeutic benefits in managing mild to moderate inflammatory conditions; however, these studies remain limited in scale and methodological rigor. In conclusion, moringa leaves show promising and multifaceted anti-inflammatory mechanisms, warranting further large-scale clinical validation to support their use as a complementary therapeutic agent.